Morphology of pupae of Synanthedon codeti (Oberthür, 1881) and Synanthedon theryi Le Cerf, 1916 (Lepidoptera: Sesiidae) - Bąkowski, Marek (Zootaxa, 2021)
This work presents the first description of the pupal morphology of the clearwing moth species Synanthedon codeti (Oberthür, 1881) and S. theryi Le Cerf, 1916.                All diagnostic morphological features are described in detail, compared with the closely related species S. vespiformis (Linnaeus, 1761), and the features are illustrated with photographs and line drawings.